MonArtMics / Mustaqim Mohammad … [et al.] - Mohammad, Mustaqim; Rosli, Adi Sufian; Yakob, Nur Balqish Hanum; Che Mohd Noor, Nur Dalila Shairah; Md.Yunus, Nor Maisyarah; Abu Hassan Asari, Fadli Fizari (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Monetary Economics is a subject which is a combination of macroeconomics, finance and mathematics concepts. This subject assists students in giving better understanding on the real economic situation. However, it is not easy for students to completely understand and memorize the whole syllabus. Therefore, our main motive for designing this mind map is to draw attention and attract interest among the students. The main uniqueness of this mind map is based on emphasis given on the interest rate concept, since it is the most vital component in the monetary system. In addition, this mind map is also unique. Compared to other mind maps, this mind map is unique given that the whole syllabus is compressed into a single piece of paper, instead of summarizing it chapter by chapter. This will give a better indulgence and shorten the learning curve for the students. It is believed that with the power of visualization, the memory will last forever. From another perspective, this innovation will help lecturers to perform better in their teaching process. As a conclusion, it is expected that this kind of innovation can help the users in the teaching and learning process, thus the real economic condition can be studied easier. It is also hoped that this mind map will be the main revision tool for all Monetary Economics lecturers and students in Malaysia and worldwide.